The challenges of using TED Talks as authentic resources of academic listening for EFL university students - Astika, Gusti; Kurniawan, Ardiyarso (Indonesian Journal of Applied Linguistics, 2020)
Developing listening skills in an academic context is essential as it requires students to acquire a sufficient number of vocabulary, which will enable them to comprehend the information provided in a text. This paper explores the challenges faced by twenty-seven EFL students in an Academic Listening course using a task-based language teaching framework (Nunan, 2004; Willis, 1996; Willis Willis, 2011). The data were collected from the students’ listening journals containing accounts of their experiences during the course. The data from the journals were analyzed qualitatively to identify the themes that emerged. The results of the analysis reveal various challenges encountered by the students: unfamiliar accents, fast speed of speech, and new vocabulary. The paper ends with a recommendation to investigate vocabulary learning strategies of spoken texts.